Studies of the hydration of polyelectrolytes. - Desnoyers, J. E. (University of Ottawa (Canada), 1961)
Three approaches to the study of hydration of polymeric ions in relation to that of analogous simple ions have been made as follows: In the first part of the thesis, information in sought regarding the hydration of polyions by evaluating the degree of dielectric saturation near the charged particles. Previously, this had been done only in the ease of isolated simple ions assumed to be point charges. Since the ionic atmosphere can never be removed from the polyions, even in very dilute solutions, the simple electrostatic field cannot be used in the evaluation of the extent of dielectric saturation. The dielectric constant has therefore been obtained directly as a function of the distance from the polyion from a solution of the Poisson-Boltzmann equation and previously published relations between dielectric constant and field intensity. The solutions have been obtained by numerical methods using a digital electronic computer. The Poisson-Boltzmann equation was solved by this method for the following models: simple ions, cylindrical polyions, spherical polyions and planar colloidal ions. The relative degrees of dielectric saturation were calculated and related to the relative extents of primary hydration for the different ionic models. The effect of dielectric saturation on the field and potential functions is also discussed for the various ion models. The second part of the thesis deals with solvent electrostriction and the determination of salting-out by polyelectrolytes. In order to interpret the experimental data obtained on the salting-out of non-electrolytes (argon, ethylene, d-1 leucine and benzamide) by polyelectrolytes (sodium polyphosphates, potassium polymethacrylate and poly-4-vinyl-N-n-butylpyridinium bromide), it was first found necessary to modify the existing salting-out theories for simple ions and a proposed theory for polymeric ions, by taking into account the effect of dielectric saturation of the solvent near the ions. Such effects are shown to be important in determining salting-out constants and, in fact, lead to the recognition of the necessity for taking into account the specific structure (e.g. effective radius) of the primary hydration shell. Other modifications to the theory are also suggested. In the modified salting-out theory referred to above, the radius of the primary hydration shell in required. The third part of the thesis therefore describes the evaluation of this parameter from experimentally measured apparent molar volumes for simple and polymeric ions. The significance of these apparent molar volumes in relation to the hydration of this polymeric and simple ions is also discussed.
Keywords: Chemistry, Inorganic.